Effect of integrated nitrogen management on growth and yield of sesame (Sesamum indicum L.): EFFECT OF INTEGRATED NITROGEN MANAGEMENT ON GROWTH AND YIELD OF SESAME - D M GHODKE; U N ALSE; S AHER; S B SURYAWANSHI (Journal of Oilseeds Research, 2014)
A field experiment was conducted during kharif season of 2011 in vertisols at Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani to study the effect of integrated nitrogen management on growth and yield of sesame varieties. The results indicated that variety AKT-101 was superior over Phule Til-1 in producing higher growth, yield attributes and yield. Among different integrated nitrogen management practices, application of recommended dose of fertilizer (60:40 N: P2O5 kg/ha) had the highest growth, yield attributes and yield of sesame which was at par with the application of 25% N through vermicompost + 75% N through urea. Gross monetary returns and net monetary returns were higher in recommended dose of fertilizer than integrated nitrogen levels. Among different varieties, AKT-101 recorded highest gross and net monetary returns.